Computational fluid dynamics simulations of Taylor bubbles rising in vertical and inclined concentric annuli. (February 2023) - Liu, Yaxin; Ozbayoglu, Evren M.; Upchurch, Eric R.; Baldino, Silvio
Highlights: Systematic investigation is carried out to study the steady-state Taylor bubble shape and rise velocity. Generating relatively large 3D numerical database of Taylor bubbles rising in an annular space. Developing correlations to predict the drift velocity of Taylor bubbles in vertical and inclined annuli. Abstract: Motivated by a dearth of research on the dynamics of single Taylor bubbles in annular conduits, a computational study of Taylor bubbles rising in vertical and inclined annuli is performed using a three-dimensional computational fluid dynamics (CFD) simulation with the Volume-of-Fluid (VOF) method implemented in the commercial software ANSYS Fluent (Release 19.2). The effects of Eötvös number ( Eo  = [10, 300]), inverse viscosity number ( Nf  = [40, 320]), and inclination angles ( θ  = {10°, 20°, 30°, …, 80°}) on the steady-state Taylor bubble shape and rise velocity are investigated. The latter is parameterized by Froude number ( Fr ) and simulations are carried out keeping constant liquid-gas density ratio and dynamic viscosity ratio at 1000 and 100, respectively. The simulation results provide good agreement with the existing numerical findings and experimental observations. For Taylor bubbles in a vertical annulus, the surface tension and liquid viscosity show significant impacts on bubble shape (length and trailing edge) and Fr for Eo  = [10, 100] and Nf  = [40, 160]. A correlation for Fr in terms of Eo and Nf is proposed and compared against 66 numerical simulations and 20 air-water experimental results available in the literature, resulting in average errors of 2.13% and 5.52%, respectively. Relatively large errors of 7.38% for characteristic dimension D*  ≤ 45 mm and 11.82% for D*  ≥ 344.9 mm are observed ( D* = Do  + Di ). The correlation exhibits improved performance with an average error of 3.5% for 45 mm ≤ D*  ≤ 214 mm relative to the only existing model. The shape of bubbles and Fr values in inclined annulus, where the bubble becomes more streamlined and unfolded, are observed to be dramatically different from those in vertical annulus. Interestingly, the wrap angle ( θwrap ) decreases linearly with the increase of inclination angle. Predictions of the dimensionless rise velocity in inclined annulus are made and successfully compared with an existing model and experimental data from the literature.